2021
DOI: 10.1038/s41467-021-26162-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of lipid droplet formation by the yeast Sei1/Ldb16 Seipin complex

Abstract: Lipid droplets (LDs) are universal lipid storage organelles with a core of neutral lipids, such as triacylglycerols, surrounded by a phospholipid monolayer. This unique architecture is generated during LD biogenesis at endoplasmic reticulum (ER) sites marked by Seipin, a conserved membrane protein mutated in lipodystrophy. Here structural, biochemical and molecular dynamics simulation approaches reveal the mechanism of LD formation by the yeast Seipin Sei1 and its membrane partner Ldb16. We show that Sei1 lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 73 publications
3
64
0
Order By: Relevance
“…Because we found no density of Ldb16 in our yeast structure, our study does not address this question. However, a recent report showing crosslinking of Ldb16 to the central helix in yeast provides support for this hypothesis 32 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because we found no density of Ldb16 in our yeast structure, our study does not address this question. However, a recent report showing crosslinking of Ldb16 to the central helix in yeast provides support for this hypothesis 32 .…”
Section: Discussionmentioning
confidence: 98%
“…Core elements of the seipin structure appear to be evolutionarily conserved in yeast, fly and human proteins 18 , 19 , 31 , 32 . The lumenal α/β-sandwich fold domain is well resolved and has similar features in all species analyzed, except for the centrally located hydrophobic helix.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, yeast seipin lacks the HH domain found in human or Drosophila seipins. However, yeast seipin binds to Ldb16 (low dye binding 16), which contains HH-like regions and supports HH function in the yeast seipin complex ( Klug et al, 2021 ).…”
Section: Ld-er Contact Sitesmentioning
confidence: 88%
“…It is difficult to overstate the contribution of yeast systematic genetics approaches to our current understanding of eukaryotic lipid metabolism and LD biology ( Radulovic et al, 2013 ). A few recent examples include: insights onto the regulated dynamics and spatial positioning of LDs during nutrient stress conditions to supply free fatty acids ( Henne et al, 2018 ; Hariri et al, 2019 ); the first mechanistic and structural descriptions of the seipin complex driving LD budding from the ER ( Klug et al, 2021 ; Arlt et al, 2022 ), and systematic screens for its regulatory partners ( Eisenberg-Bord et al, 2018 ); the description of specific mechanisms by which LDs contribute to manage protein aggregates ( see also below ) ( Moldavski et al, 2015 ); or the discovery of a new class of LDs stemming from nuclear membranes ( Romanauska and Köhler, 2018 ). Innovative applications of imaging technologies for automated screening, such as 3D imaging ( Lv et al, 2019 ), have also been reported in this system.…”
Section: Ld Functional Genomics: Screening For Ld Biogenesis Function...mentioning
confidence: 99%